Áreas Fontes dos Minerais Pesados e sua Distribuição sobre a Plataforma Continental Sul-brasileira, Uruguaia e Norte-argentina - CORRÊA, IRAN CARLOS STALLIVIERE; ZOUAIN, RICARDO NORBERTO AYUP; WESCHENFELDER, JAIR; TOMAZELLI, LUIZ JOSÉ (Pesquisas em Geociências, 2008)
The heavy mineral fraction of sedimentary rocks and sediments can provide important information about provenance in sedimentary basins studies because some minerals or group of minerals can be traced to a source rock or terrain of specific composition. This work is a provenance study based on heavy mineral analyses of samples collected on the Rio Grande do Sul (southern Brazil), Uruguay and north of Argentine continental shelf (between 29º30´ and 37º 30´ south latitude and 48º 30´ and 56º 30´ west longitude). The fine and very fine sand fractions (2-4 Φ) were selected for heavy mineral analysis employing bromoform (S.G.= 2.65). The quantitative analysis was made using a microscope for the mineral identification and the counting of 300 grains from each sample, in a total of 106 samples. Multivariate data analysis was applied for mineralogical analysis, principally the RQmode vector. Four principal assemblages were defined applying this technique revealing the main source as well as the dispersal patterns for the sediments. The first component was dominated by augite indicating a panpean-patagonic source. The second component was dominated by hornblende and hypersthene minerals, indicating a provenance from Precambrian terrains with basaltic influence. The third component was marked by the dominance of tourmaline, staurolite, epidote and kyanite reflecting a source from the Precambrian metamorphic terrains. Finally, the four components with apatite, zircon and sillimanite minerals were dispersed by the Rio de La Plata system.